Pengaruh Brand Image dan Iklan Terhadap Perilaku Pembelian Konsumen Pada Mixue Cabang Cifest Cikarang - Fatin Salsabila; Muhammad Muadz Al Qarny; Mutty Destianty Putry; Luthfiah Istiqomah; Retno Purwani Setyaningrum (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of brand image and advertising on consumer purchasing behavior at Mixue Jababeka Branch. Mixue is a popular beverage and ice cream brand in Indonesia, known for its creative and massive marketing strategy on social media. This research used a quantitative approach with a survey method involving 70 respondents who are Mixue consumers. The instrument used was a Likert-scale questionnaire. The results indicate that brand image and advertising have a positive relationship with consumer purchasing behavior. However, their influence is not statistically significant, suggesting that other factors such as price, product quality, and social recommendations should also be considered in understanding consumer purchase decisions. This research is expected to provide insights for business practitioners in formulating more targeted marketing strategies.